Health Information Management System for Elderly Health Sector: A Qualitative Study in Iran - Sadoughi, Farahnaz (Iran Red Crescent Med J, 2016)
BACKGROUND: There are increasing change and development of information in healthcare systems. Given the increase in aging population, managers are in need of true and timely information when making decision. OBJECTIVES: The aim of this study was to investigate the current status of the health information management system for the elderly health sector in Iran. MATERIALS AND METHODS: This qualitative study was conducted in two steps. In the first step, required documents for administrative managers were collected using the data gathering form and observed and reviewed by the researcher. In the second step, using an interview guide, the required information was gathered through interviewing experts and faculty members. The convenience, purposeful and snowball sampling methods were applied to select interviewees and the sampling continued until reaching the data saturation point. Finally, notes and interviews were transcribed and content analysis was used to analyze them. RESULTS: The results of the study showed that there was a health information management system for the elderly health sector in Iran. However, in all primary health care centers the documentation of data was done manually; the data flow was not automated; and the analysis and reporting of data are also manually. Eventually, decision makers are provided with delayed information. CONCLUSIONS: It is suggested that the steward of health in Iran, the ministry of health, develops an appropriate infrastructure and finally puts a high priority on the implementation of the health information management system for elderly health sector in Iran.